Kompetencje socjokulturowe jako problem w nauczaniu głuchych języka polskiego. Uwagi na marginesie komunikacji internetowej niesłyszących - Ruta, Karolina; Wrześniewska-Pietrzak, Marta (Poznańskie Spotkania Językoznawcze, 2015)
The article discusses the problem of teaching Polish as a foreign language to hearing impaired persons – therefore it should be considered as an item of the glottodidactic research cycle. The subject of the analysis are emails and other written communications of persons with hearing impairment posted at Internet forums. The aim of the analyses is to present problematic areas in the Polish language which are visible in the material gathered. These areas refer to the so called socio-cultural competence which forms a part of communicative competence. Problems spotted refer not only to the inability to use a correct variation of the Polish language, but also to the lack of command of courteous forms which should appear in communication with persons of unknown or superior status. Causes of the difficulties observed in written communications posted by hearing impaired persons should be tracked back not only to the lack of appropriate didactical offer, but mostly to the cultural separation between the deaf and the hearing persons.